2023
DOI: 10.3390/jimaging9080163
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Based Effective Ensemble Frameworks for Predicting Human Brain Tumor

Farhana Khan,
Shahnawaz Ayoub,
Yonis Gulzar
et al.

Abstract: The diagnosis of brain tumors at an early stage is an exigent task for radiologists. Untreated patients rarely survive more than six months. It is a potential cause of mortality that can occur very quickly. Because of this, the early and effective diagnosis of brain tumors requires the use of an automated method. This study aims at the early detection of brain tumors using brain magnetic resonance imaging (MRI) data and efficient learning paradigms. In visual feature extraction, convolutional neural networks (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Gulzar and Khan [ 72 ] conducted a comparative study on U-Net and attention-based methods for skin lesion image segmentation, attaining 92.11% accuracy with a superior hybrid TransUNet. Khan et al [ 73 ] proposed an ensemble (XG-Ada-RF) on extreme gradient boosting, Ada-boost, and random forest, achieving 95.9% accuracy for tumor detection and 94.9% for normal brain tumor images. Mehmood et al [ 74 ] presented SBXception, a modified model for the HAM10000 dataset, achieving 96.97% accuracy on a holdout test set.…”
Section: Related Workmentioning
confidence: 99%
“…Gulzar and Khan [ 72 ] conducted a comparative study on U-Net and attention-based methods for skin lesion image segmentation, attaining 92.11% accuracy with a superior hybrid TransUNet. Khan et al [ 73 ] proposed an ensemble (XG-Ada-RF) on extreme gradient boosting, Ada-boost, and random forest, achieving 95.9% accuracy for tumor detection and 94.9% for normal brain tumor images. Mehmood et al [ 74 ] presented SBXception, a modified model for the HAM10000 dataset, achieving 96.97% accuracy on a holdout test set.…”
Section: Related Workmentioning
confidence: 99%
“…Ensemble models have been proposed by some researchers to detect brain tumor types [1,[37][38][39][40][41][42]. Aurna et al [1] proposed a two-stage method for brain tumor classification.…”
Section: Related Workmentioning
confidence: 99%
“…In their study, Patil and Kirange [39] combined SCNN and VGG16 models in the feature extraction phase using ensemble learning. Extreme Gradient Boosting, Ada-Boost, and Random Forest (XG-Ada RF) are three high-performance individual machine learning models that Khan et al [40] suggested as an ensemble for binary classification. Tantel et al [41] combined five CNN (AlexNet, VGG16, ResNet18, GoogleNet, and ResNet50) architectures with ensemble techniques for binary tumor classification.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, the pervasive influence of artificial intelligence (AI) has become increasingly apparent, bringing about transformative changes across a spectrum of fields and enriching various facets of our everyday existence [4,5]. It has redefined how we approach education [6], fine-tuned financial strategies [7], simplified agricultural workflows [8][9][10][11][12][13][14][15][16], and elevated healthcare diagnostics to new heights [17][18][19][20][21][22][23]. As it seamlessly integrates into these diverse sectors, AI continues to demonstrate its capacity for generating unparalleled efficiencies, refining decision-making procedures, and addressing intricate challenges with a precision derived from data-driven insights [24,25].…”
Section: Introductionmentioning
confidence: 99%